Expression of ABSCISIC ACID INSENSITIVE 4 (ABI4) in developing Arabidopsis seedlings - Shkolnik-Inbar, Doron (Landes Bioscience, 2011)
We have recently demonstrated that the transcription factor ABSCISIC ACID INSENSITIVE 4 (ABI4) mediates abscisic acid and cytokinin inhibition of lateral root formation by reducing polar auxin transport in Arabidopsis thaliana.1 In that study, we provided a direct demonstration of ABI4 expression in phloem companion cells and parenchyma of the vascular system in the mature regions of the roots. Although also studied in mature plants, ABI4 has been studied primarily in germinating seedlings and its expression has been assumed by some researchers to be restricted to early germination stages. We thus constructed transgenic Arabidopsis plants expressing an ABI4:GUS construct, and followed ABI4 promoter activity during seedling development, focusing on the roots.